Pengaruh Pemberian Jus Jambu Biji Merah dan Kurma Terhadap Peningkatan Kadar HB pada Ibu Post Partum - Rini Anggeriani; Mona Yatiliu (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2020)
The Data in 2017 from World Health Organization (WHO) on national health status at the target of the Sustainable Development Goals (SDGs) stated globally around 830 women die every day due to complications during pregnancy and childbirth, with an MMR rate of 216 per 100,000 live births. As much as 99 percent of maternal deaths due to problems of pregnancy, and childbirth or childbirth happened in developing countries. Anemia was a condition in which red blood cells (erythrocytes) decrease in the blood circulation or the mass of hemoglobin so that it was unable to fulfill its function as a carrier of oxygen throughout the tissue. The purpose of this study was to determine the effect of the administration of red guava juice and dates palm to increase Hb levels in post partum mothers. This study used a pre-experimental research design with a one group pre-test post-test approach. With sampling was taken by purposive sampling. The Data analysis using univariate, bivariate analysis using paired t-test. The results showed that 15 postpartum mothers who experienced anemia had a p value of 0,000 ≤ 0.05 so it can be concluded that there was an effect of giving red guava juice and dates to post partum mothers who had anemia. It is expected for post partum mothers who are anemic to consume red guava juice and dates routinely in order to increase Hb levels in the body.